Lentiviral vectors for the treatment of primary immunodeficiencies. Issue 4 (12th March 2014) - Farinelli, Giada; Capo, Valentina; Scaramuzza, Samantha; Aiuti, Alessandro
Abstract: In the last years important progress has been made in the treatment of several primary immunodeficiency disorders (PIDs) with gene therapy. Hematopoietic stem cell (HSC) gene therapy indeed represents a valid alternative to conventional transplantation when a compatible donor is not available and recent success confirmed the great potential of this approach. First clinical trials performed with gamma retroviral vectors were promising and guaranteed clinical benefits to the patients. On the other hand, the outcome of severe adverse events as the development of hematological abnormalities highlighted the necessity to develop a safer platform to deliver the therapeutic gene. Self‐inactivating (SIN) lentiviral vectors (LVVs) were studied to overcome this hurdle through their preferable integration pattern into the host genome. In this review, we describe the recent advancements achieved both in vitro and at preclinical level with LVVs for the treatment of Wiskott‐Aldrich syndrome (WAS), chronic granulomatous disease (CGD), ADA deficiency (ADA‐SCID), Artemis deficiency, RAG1/2 deficiency, X‐linked severe combined immunodeficiency (γchain deficiency, SCIDX1), X‐linked lymphoproliferative disease (XLP) and immune dysregulation, polyendocrinopathy, enteropathy, X‐linked (IPEX) syndrome.